Level of antibody to hepatitis B surface antigen declined below 10 mIU/ml is still protective - Ping Shen; Chengyu Xu; Taishun Li; Yanjing Rui; Yali Hu; Yingwei Zhang; Yi-Hua Zhou (npj Vaccines)
Abstract Whether declined level <10 mIU/ml of antibody to hepatitis B surface antigen (anti-HBs) is still immune to hepatitis B virus (HBV) is controversial. We longitudinally investigated hepatitis B markers in 395 vaccinated children of HBV-infected mothers at a 5.4-years interval. At baseline, they were at average age of 3.2 ± 1.8 years (0.6–12), and 106 (26.8%) children had anti-HBs <10 mIU/ml and 289 (73.2%) others had anti-HBs ≥10 mIU/ml. Of them, 84 (21.3%) were boosted with hepatitis B vaccine and 311 (78.7%) were not boosted. When they were at the age of 8.6 ± 1.9 years (6–18), 166 (42.1%) had anti-HBs <10 mIU/ml and 229 (57.9%) had anti-HBs ≥10 mIU/ml, and none was infected with HBV, including 62 unboosted children with anti-HBs <10 mIU/ml at baseline. Of 311 unboosted participants, 48 (15.4%) had increased anti-HBs levels in the absence of antibody to hepatitis B core antigen, suggesting natural booster immunization. Considering the close contact of children to their HBV-infected mothers, our study showed that successfully vaccinated children are still immune to HBV, even after the anti-HBs levels dropped to <10 mIU/ml. Therefore, anti-HBs levels <10 mIU/ml should not be an indication for booster hepatitis B vaccination.